2011
DOI: 10.1051/0004-6361/201116758
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the shocks in BHR71: new observational constraints and H2O predictions forHerschel

Abstract: Context. During the formation of a star, material is ejected along powerful jets that impact the ambient material. This outflow phenomenon plays an important role in the regulation of star formation. Understanding the associated shocks and their energetic effects is therefore essential to the study of star formation. Aims. We present comparisons of shock models with observations of H 2 and SiO emission in the bipolar outflow BHR71. Such comparisons constitute a good way to constrain the type, velocity and age … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

7
2

Authors

Journals

citations
Cited by 26 publications
(41 citation statements)
references
References 51 publications
4
37
0
Order By: Relevance
“…This is consistent with the fact that the SiO emission detected so far in low-mass star-forming regions is associated with high-velocity protostellar outflows, either as broad SiO emission, or as narrow emission with a velocity peak offset from systemic velocities (e.g. Gueth et al 1998;Nisini et al 2007;Gusdorf et al 2011;Gómez-Ruiz et al 2013).…”
Section: Origin Of the Narrow Sio Emissionsupporting
confidence: 85%
“…This is consistent with the fact that the SiO emission detected so far in low-mass star-forming regions is associated with high-velocity protostellar outflows, either as broad SiO emission, or as narrow emission with a velocity peak offset from systemic velocities (e.g. Gueth et al 1998;Nisini et al 2007;Gusdorf et al 2011;Gómez-Ruiz et al 2013).…”
Section: Origin Of the Narrow Sio Emissionsupporting
confidence: 85%
“…These slow shocks are similar to shocks originating in bipolar outflows of very young stars (e.g. Gusdorf et al 2011): they strongly cool through molecular emission and can be observed in the far-IR and sub-mm wavelength regime (e.g. Neufeld et al 2007;Frail & Mitchell 1998).…”
Section: Introductionmentioning
confidence: 60%
“…For instance, a microjet was recently imaged at high spatial resolution in the HH212 protostellar outflow by Codella et al (2014) in SiO and Podio et al (2015) in SO and SO 2 , without having a counterpart in H 2 emission at 2.12 µm. Our modelling method is the same as presented in Gusdorf et al (2011Gusdorf et al ( , 2012. The model is one-dimensional, can simulate the propagation of stationary C-and J-type shocks, and includes a self-consistent Large Velocity Gradient (LVG) treatment of the radiative transfer in the lines emitted by various cooling species (CO, H 2 O, SiO, NH 3 , and OH).…”
Section: Discussionmentioning
confidence: 99%